Renal ischemia--reperfusion injury: an inescapable event affecting kidney transplantation outcome - Böhmová, R; Viklický, O (Folia microbiologica, 2001)
Ischemia--reperfusion (I-R) injury has been shown to be a common cause of late and irreversible complications during a variety of standard medical and surgical procedures. The pathogenesis of events which follow the I-R involves both injured endothelium and activated leukocytes and their interaction. In kidney transplantation, an I-R injury occurs in situations such as graft harvesting, cold storage and surgery. Clinical consequences of I-R injury have been considered to be delayed graft function and acute rejection in the short term and chronic rejection late after transplantation. Here we focused on current knowledge of pathophysiology of renal I-R injury in kidney transplantation and on possibilities of experimental therapy.
Keywords: rejekce štěpu; výsledek terapie; Kidney Transplantation; Reperfusion Injury; Kidney Diseases; Treatment Outcome; Kidney; lidé; nemoci ledvin; Graft Rejection; transplantace ledvin; ledviny; reperfuzní poškození; Humans